(untitled) (International Journal of Food and Nutritional Sciences, 2022)
One of the biggest revolutions of modern history is the invention of agriculture for a healthier lifestyle. It significantly changed the human culture and played an important role in the development of the population and biological improvements in food production and domestication. The frequency of pests on food crops increased because environmental circumstances were changing, and diseases on crops increased rapidly. These diseases inflict catastrophic social, economic, and ecological casualties, and this extraordinary challenge is a concern for the correct and prompt detection of diseases. In this contest, IT (Information Technology) has left its mark on the potential of farmers and is still to be exploited. As input for making the right decision, farmers need timely and credible sources of knowledge. Study into agriculture is then planned by improving the disease diagnostics method with the use of newer information technology to enhance efficiency and quantity for agricultural production and its allied operation. Early forecasting of disease epidemics will help farmers to choose the right fertilizer, pesticides, and fungicides in the right amount. In this paper, we discussed and surveyed various research articles based on paddy crops disease detection and classification of exiting methods that will make use of a future framework for developing a disease predicting model using weather parameters associated with the development of the disease outbreak.